Role of chloride ion in hydroxyl radical production in photosystem II under heat stress: electron paramagnetic resonance spin-trapping study - Yadav, Deepak Kumar; Pospíšil, Pavel (Journal of bioenergetics and biomembranes, 2012)
Hydroxyl radical (HO•) production in photosystem II (PSII) was studied by electron paramagnetic resonance (EPR) spin-trapping technique. It is demonstrated here that the exposure of PSII membranes to heat stress (40 °C) results in HO• formation, as monitored by the formation of EMPO-OH adduct EPR signal. The presence of different exogenous halides significantly suppressed the EMPO-OH adduct EPR signal in PSII membranes under heat stress. The addition of exogenous acetate and blocker of chloride channel suppressed the EMPO-OH adduct EPR signal, whereas the blocker of calcium channel did not affect the EMPO-OH adduct EPR signal. Heat-induced hydrogen peroxide (H₂O₂) production was studied by amplex red fluorescent assay. The presence of exogenous halides, acetate and chloride blocker showed the suppression of H₂O₂ production in PSII membranes under heat stress. Based on our results, it is proposed that the formation of HO• under heat stress is linked to uncontrolled accessibility of water to the water-splitting manganese complex caused by the release of chloride ion on the electron donor side of PSII. Uncontrolled water accessibility to the water-splitting manganese complex causes the formation of H₂O₂ due to improper water oxidation, which leads to the formation of HO• via the Fenton reaction under heat stress.
Keywords: Heating; fotosystém II (proteinový komplex); Electron Spin Resonance Spectroscopy; Hydrogen Peroxide; Spin Trapping; hydroxylový radikál; oxidace-redukce; peroxid vodíku; elektronová paramagnetická rezonance; chloridy; spin trapping; Oxidation-Reduction; Chlorides; Photosystem II Protein Complex; Hydroxyl Radical; vytápění; Spinacia oleracea